Beyond Bifurcation: Emotional Coherence and Audience Subjectivity in the Parallel Narratives of Look Both Ways (2022) - Aisyah Akilah; Maridah Nurhasanah; Yanti Rosalinah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Parallel storytelling has become a prominent narrative mode in 21st-century cinema, reflecting a modern consciousness saturated with potentialities and choices. While existing scholarship has extensively mapped the structural mechanics (e.g., editing, montage) and cognitive effects (e.g., audience engagement) of narrative bifurcation, a significant gap remains in understanding how this form constructs a unified emotional coherence and fosters a specific subjective position for the viewer within divergent timelines. This study addresses this gap through a qualitative narrative analysis of the Netflix film Look Both Ways (2022). Employing an interdisciplinary framework that synthesizes narrative theory, affective studies, and social constructionism, the analysis reveals that the film’s dual narratives are not merely alternative realities but simultaneous emotional truths. The film achieves this through the meticulous integration of visual style (color palette, setting), narrative typography, and sound design, which function as a cohesive system of subjective cues. These elements guide the audience to navigate both timelines not as a dispassionate observer of branching paths, but as an empathetic participant in the protagonist’s holistic emotional journey. The study concludes that in Look Both Ways, bifurcation transcends its structural function to become an internalized emotional logic, offering a nuanced cinematic model for representing the lived experience of choice, anxiety, and self-discovery in contemporary life. This reframing contributes to film narrative theory by prioritizing phenomenological engagement over structural taxonomy. This study ultimately highlights that qualitative narrative analysis is the most appropriate method for examining how visual, auditory, and textual elements interrelate to produce emotional coherence across dual timelines, offering a more integrated understanding of parallel storytelling in contemporary film.